The theme of disappearance and renewal in the poetry of Wilhelm Lehmann : a thesis presented in partial fulfillment of the requirements for the degree of Master of Arts in German at Massey University - Newrick, Brian Allan (Massey University, 1978)
Since the beginning of time, Man has been preoccupied with the fleetingness of physical existence. Although concerned by the inevitability of the passing of materiality, he accepted it as a part of a permanent world order. However, as a result of the gradual disintegration of belief in a divinely based system, from the end of the Middle Ages until the present day, Man has become increasingly conscious of the transitoriness of material existence. Accompanying this disintegration, a growing feeling of isolation from the "Whole" has arisen. This sense of alienation is shared and articulated by the German poet Wilhelm Lehmann. Lehmann comments upon the position of Man in his critical essay Kunst als Jubel der Materie: Wir wurden aus dem Paradies der alten Einheit vertrieben. Diese Vertreibung bedeutet den Beginn des Dichtens, des Schreibens. Wir verloren das Ganze, wir wurden selbst Teil, um uns als Teil des Ganzen zu erinnern und uns seiner in der Sehnsucht zu vergewissern. Hesiodisch gesprochen: das Halbe ist mehr als das Ganze. Welches ist das Geschäft der Welt? Da zu sein. Welches ist das Geschäft der Dichtung? Der welt bei diesem Vorhaben zu helfen. Dichtung ist nicht Flucht, sondern Vorhandenheit, sie ist Kraft, also Gegenwart. Daher Schall, Metrum, Rythmus, Keim innerhalb der Zeile so gut wie an ihrem Ende, Formwille, also Sprache innerhalb der Sprache als Tag innerhalb des Tages. Der Welt als der Welt innezuwerden, erfand sich die Natur die Sprache, die Dichtung. ¹ Wilhelm Lehmann: Sämtliche Werke in drei Bänden. Bd. III, Gutersloh, 1962. p.159. Henceforth referred to as SW III.) As a precondition for Man's reintegration into the "Whole", physical existence must be re-endowed with the permanence it has lost through conceptualisation. This can be achieved, according to Lehmann, through poetry. He believes poetry to be "die Blutspenderin des verfallenden Lebens."² Ibid. p.374) Within the poem, the things of Nature, although having ceased to exist as physical entities, can live once more. The Poet, through his art, can rescue them from oblivion. [From Introduction]
Some German throughout.
Keywords: 20th Century German Poets; Lehmann, Wilhelm 1882 -1968; History and criticism; Criticism and interpretation